2017
DOI: 10.2355/isijinternational.isijint-2017-054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Dissolution Reaction on Wetting Behaviour of Molten Fe–C Alloy on Graphite Substrate in the Initial Contact Period

Abstract: A wetting behaviour of Fe-C sample on carbonaceous materials has been extensively investigated to understand the liquid flow behaviour in lower part of blast furnace. The previous studies reported a large change in apparent contact angle in the initial contact period in the wetting between the Fe-C sample and the carbonaceous materials substrate. The carbon dissolution reaction and the interfacial morphology in the initial contact period would strongly affect the wetting behaviour in this period. To further un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…[5,16] Rather this was an ex situ method to compare the different metal-crucible interactions and to determine the effectiveness of the mitigation technique. Though the metal was contained in crucibles rather than flat substrates, this procedure was not dissimilar to the quenching method used by Nguyen et al [17] Upon cooling, samples were sectioned in half vertically, mounted in epoxy, and polished to measure the angle of contact between the metal and crucible. Representative measurements are shown in Figure 3 of the metal with graphite crucibles and MgO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,16] Rather this was an ex situ method to compare the different metal-crucible interactions and to determine the effectiveness of the mitigation technique. Though the metal was contained in crucibles rather than flat substrates, this procedure was not dissimilar to the quenching method used by Nguyen et al [17] Upon cooling, samples were sectioned in half vertically, mounted in epoxy, and polished to measure the angle of contact between the metal and crucible. Representative measurements are shown in Figure 3 of the metal with graphite crucibles and MgO.…”
Section: Methodsmentioning
confidence: 99%
“…The angles were measured in a similar way to that in the literature. [17,18] Because MgO filled the crucibles, the angle measured was between the top surface of the metal and the crucible wall.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, sessile drop method, 36,54,55) captive bubble method, 38,56,57) environmental scanning electron microscopy (ESEM) method 44,52,58,59) and gel trapping method 45,47) are direct methods. These methods obtain contact angles by observing the forming angles directly based on the theory of Young.…”
Section: Direct Methodsmentioning
confidence: 99%
“…According to the information of reduction degree, microstructure observation and remained carbon of reduced iron, it can be concluded that metallic iron was formed, carburization was occurred, and part of metallic iron was melted into droplets. References [17][18][19][20] reported that when the amount of carbon dissolved in liquid iron is increased, the contact angle between liquid iron and carbon substrate is increased accordingly. In other words, the wettability is lowered as the carburization of reduced iron increases.…”
Section: Influence Of C/o On Reduction and Morphologymentioning
confidence: 99%